ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DEWAN DIREKSI, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI TAHUN 2011-2014 - Diana Gustinya, SE., M.Ak. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This study aims to examine corporate governance mechanism, institusional ownership, independent of commissioner, size board of director, and also firm size and leverage to earning management. The sample in this study were non- financial companies listed in IDX (Indonesia Stock Exchange) in the periode 2011-2014. The number of sample used were 152 companies listed were taken by purposive sampling. The method of analysis of this research used multi regression and single regression with SPSS 22 Program. The results of this research show that, (1) institusional ownership had negative significant influence to earnings management, (2) independent of commissioner had positif not significant influence to earning management,(3) size board of director had negative not significant influence to earnings management, (4) leverage had negatif not significant influence to earnings management, (5) firm size had negative not significant influence to earnings management.